EVALUASI KEBIJAKAN KETAHANAN PANGAN DI PROVINSI RIAU (Studi Kasus di Kabupaten Kampar) - Kartini, Nina; As’ari, Hasim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The creation of food security conditions is fundamental in realizing human development. However, the food security still poses various problems that have not been resolved until now, where the condition of food vulnerability is very related to food security. Food security Policy is one solution to overcome food vulnerability problem. Riau Province, one of the provinces that issued a food security policy with the formation of regional regulation of Riau Province No. 13 of 2018 about food security makes this research focus on highlighting the implementation of Food security Policy. The implementation of the policy in this case is the food security Service of Riau Province and the Food security Service Kampar District, which is examined by using the Terori evaluation policy according to Dunn (2018:115) and Jones quoted by Kawengian & Rares (2015). The method used in this research is a qualitative method with a case study approach. In the final process, the results showed the implementation of the food security policy that has not been optimal encountered various constraints in the implementation of food security policy are: communication, regulation, community economy, and access. Keyword: Policy Evaluation , Food Security, and Food Vulnerability.